Design and implementation of pulse width modulation gate control signals for two-level three-phase inverters - Aboadla, Ezzidin Hassan; Kadir, Kushsairy; Khan, Sheroz (Institute of Advanced Engineering and Science, 2024)
The switching control circuit in a DC to AC inverter is the critical part that is applied to control the power transistors insulated-gate bipolar transistor (IGBTs) and metal-oxide semiconductor field-effect transistor (MOSFETs). This paper proposes a high-performance and low-cost pulse width modulation (PWM) control signal with a 120º phase shift circuit for a two-level three-phase inverter. Typically, a PWM signal with a 120º phase shift for three-phase inverters is generated with the help of analogue components with more complicated designs and power losses or by using a microcontroller with necessary programming or coding. The proposed solution is to design a 120° three-phase shift circuit based on D flip-flops and the 555-timer to generate the clock signal for the flip-flop input in addition to the dead-time control circuit. The proposed circuit is controlled by one square wave signal as an input signal to generate six output PWM control signals at 50 Hz to operate six MOSFETs in the three-phase inverter. Simulation results in power simulation software PSIM and PROTEUS simulation tools are used to verify the proposed circuit. Hardware implementation of the proposed circuit and three-phase inverter is carried out to validate the performance of the proposed design.